An Analysis of Green Environment Alerting Bot - B.Kiran Bala1, K.Premitha2, D.Shiporal Shiny3, S.Priyadharshini4, S.Reetha Dhevi 5 (International Journal of Advanced Science and Technology, 2020)
The present environment pollution is very high in all over the world and to support the society and people for live update and safety purpose. This analysis is mainly used to find out the humidity inside the room as well as outside the room, heat and temperature of the room it is very important feature of this system and it will act as a fire alter and gas leakage in the room can also be separated and identify from the room in the environment by alerting the users is the main objective of this system and for that process this system is used bot technology with the help of raspberry pi technology and users come to know the sudden change in present environment through beep so that users can be alter and take precaution steps to make safe themselves and the society.